Blood transfusion does not adversely affect survival after elective colon cancer resection: a propensity score analysis - Tarantino, Ignazio; Ukegjini, Kristjan; Warschkow, René; Schmied, Bruno M.; Steffen, Thomas; Ulrich, Alexis; Müller, Sascha A. (Langenbeck's archives of surgery, 2013)
The aim of this study was to assess the putative impact of perioperative blood transfusions on overall survival in patients undergoing curative resection for stage III colon cancer by applying propensity scoring methods. Methods: In a single-center study, a total of 309 patients who underwent open curative resection for stages I–III colon cancer from 1996–2008 were assessed. The mean follow-up period was 47 ± 38 months. Transfused and non-transfused patients were compared using both Cox regression and propensity score analyses. Results: Overall, 148 patients (47.9 %) received blood transfusions. The patient characteristics were highly biased toward transfusions (propensity score 0.68 ± 0.22 vs. 0.30 ± 0.22, p <0.001). In the unadjusted analysis, blood transfusions were associated with a 90 % increased risk of overall mortality (hazard ratio 1.90, 95 % CI: 1.19–3.04, p = 0.001). The 5-year survival for patients receiving blood transfusions was 64.5 % (95 % CI: 56.0–74.3 %) compared with 80.1 % (95 % CI: 72.8–88.2 %) in those not receiving blood transfusions. In the propensity score-adjusted Cox regression analysis (hazard ratio: 0.85, 95 % CI = 0.53–1.37, p = 0.501), blood transfusions did not increase the risk of overall mortality. After risk adjustment, the 5-year survival rate for patients receiving blood transfusions was 66.6 % (95 % CI: 57.4–77.3 %) compared with 61.8 % (95 % CI: 51.9–73.7 %) for those who did not. Conclusion: This study is the first propensity score-based analysis that provides evidence that poor oncological outcomes after curative colon cancer resection in patients receiving perioperative blood transfusions are due to the clinical circumstances that require the transfusions and are not due to the blood transfusions.
Gesehen am 31.01.2022